Supply chain optimization for Ocean Alkalinity Enhancement: A Norwegian case study - Martine Lindland; Emmiche Advocaat Wigand; Kjetil Fagerholt; Frank Meisel; Lisa Herlicka (International Journal of Greenhouse Gas Control, 2025)

A network design problem for upgrading decentrally produced biogas into biomethane - Daniel Schröer; Lisa Herlicka; Arne Heinold; Uwe Latacz-Lohmann; Frank Meisel (Journal of Cleaner Production, 2024)

Modeling a supply chain for carbon capture and offshore storage—A German–Norwegian case study - Anders Bennæs; Martin Skogset; Tormod Svorkdal; Kjetil Fagerholt; Lisa Herlicka; Frank Meisel; Wilfried Rickels (International Journal of Greenhouse Gas Control, 2024)

Eco‐labeling of freight transport services: Design, evaluation, and research directions - Thomas Kirschstein; Arne Heinold; Martin Behnke; Frank Meisel; Christian Bierwirth (Journal of Industrial Ecology, 2022)
The idea of eco‐labeling is to provide customers with an easy‐to‐understand signal regarding the ecological impact of using a product or service. With this paper, we propose an eco‐labeling system for freight transportation. We discuss design options based on a common emission reporting standard and a related communication protocol. We further explain a procedure for deriving labels for shipments of goods and provide examples illustrating and evaluating the labeling process at selected land‐based freight transport services. Results indicate that eco‐labels can grade the environmental impact of a transport service reliably, even if heterogeneous goods are moved together. Finally, we outline challenges for future research associated with eco‐labeling in freight transportation markets.

Relics of eclogite facies metamorphism in the Austroalpine basement, Hochgrssen (Speik complex), Austria - G. Hoinkes; S. W. Faryad; J. Puhl; W. Frank; F. Melcher; T. Meisel (Mineralogy and Petrology, 2002)